Genomewide analysis of admixture and adaptation in the Africanized honeybee. Issue 14 (24th April 2017) - Nelson, Ronald M.; Wallberg, Andreas; Simões, Zilá Luz Paulino; Lawson, Daniel J.; Webster, Matthew T.
Abstract: Genetic exchange by hybridization or admixture can make an important contribution to evolution, and introgression of favourable alleles can facilitate adaptation to new environments. A small number of honeybees ( Apis mellifera ) with African ancestry were introduced to Brazil ~60 years ago, which dispersed and hybridized with existing managed populations of European origin, quickly spreading across much of the Americas in an example of a massive biological invasion. Here, we analyse whole‐genome sequences of 32 Africanized honeybees sampled from throughout Brazil to study the effect of this process on genome diversity. By comparison with ancestral populations from Europe and Africa, we infer that these samples have 84% African ancestry, with the remainder from western European populations. However, this proportion varies across the genome and we identify signals of positive selection in regions with high European ancestry proportions. These observations are largely driven by one large gene‐rich 1.4‐Mbp segment on chromosome 11 where European haplotypes are present at a significantly elevated frequency and likely confer an adaptive advantage in the Africanized honeybee population. This region has previously been implicated in reproductive traits and foraging behaviour in worker bees. Finally, by analysing the distribution of ancestry tract lengths in the context of the known time of the admixture event, we are able to infer an average generation time of 2.0 years. Our analysis highlights the processes by which populations of mixed genetic ancestry form and adapt to new environments. Abstract : see also the Perspective by Harpur